2003
DOI: 10.1074/jbc.m209292200
|View full text |Cite
|
Sign up to set email alerts
|

β2 Subunit Propeptides Influence Cooperative Proteasome Assembly

Abstract: Vertebrate proteasomes are structurally heterogeneous, consisting of both "constitutive" (or "standard") proteasomes and "immunoproteasomes." Constitutive proteasomes contain three ubiquitously expressed catalytic subunits, Delta (␤1), Z (␤2), and X (␤5), whereas immunoproteasomes contain three interferon-␥-inducible catalytic subunits, LMP2 (␤1i), MECL (␤2i), and LMP7 (␤5i). We recently have demonstrated that proteasome assembly is biased to promote immunoproteasome homogeneity when both types of catalytic su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
112
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(127 citation statements)
references
References 38 publications
14
112
1
Order By: Relevance
“…Nevertheless, mixed proteasome populations exist in vivo (25). Importantly, the mecl1 subunit is not required for the efficient incorporation of lmp2 or lmp7 (29). Presentation of the NP 118 -126 L d -restricted epitope is enhanced in cells expressing three immunosubunits or in cells coexpressing mecl1 and lmp2 (30).…”
Section: Discussionmentioning
confidence: 91%
“…Nevertheless, mixed proteasome populations exist in vivo (25). Importantly, the mecl1 subunit is not required for the efficient incorporation of lmp2 or lmp7 (29). Presentation of the NP 118 -126 L d -restricted epitope is enhanced in cells expressing three immunosubunits or in cells coexpressing mecl1 and lmp2 (30).…”
Section: Discussionmentioning
confidence: 91%
“…Additionally, low basal β1i/LMP2 level allowed for the incorporation of β2i/MECL-1 into proteasome complexes derived from HeLa A2+/β2i and HeLa A2+/β5i/β2i cells (Supporting Information Fig. 1A) [25][26][27][28]. Therefore, the HeLa A2+ transfectants represent a useful tool to dissect the role of the different immunosubunits in MART-1 26-35 epitope processing.…”
Section: Resultsmentioning
confidence: 99%
“…In vitro studies employing high-affinity MART-1-specific CD8 + T-cell clones demonstrated that some melanoma cell lines, despite expression of MART-1 and the corresponding HLA allele, were only barely recognized by specific T cells [3]. While different variants of the MART-1 epitope (including the MART-1 [26][27][28][29][30][31][32][33][34][35] 10-mer and the MART-1 27-35 9-mer) have been identified, only the 9-mer epitope can be eluted in significant amounts from the cell surface of melanoma cells [4]. This suggests that mechanisms related to antigen processing interfere with efficient generation of the 10-mer MART-1 [26][27][28][29][30][31][32][33][34][35] epitope in tumor cells.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations